Penerapan Norma dan Etika Serta Pendampingan Pelatihan Kepemanduan Bahasa Asing - Amelia, Viona (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The application of norms in managing tourist villages is a crucial aspect that is often overlooked. The lack of clear information regarding the ethical rules and community norms has led to uncontrolled tourist behavior. This situation has caused socio-cultural impacts, including violations of local values and ethics that threaten the existing local wisdom embedded in the community’s social and cultural life. The implementation of ethics and norms is expected to increase the awareness of Tegal Loegood Tourism Village residents regarding the importance of formulating and disseminating village tourism regulations. In addition to fostering public awareness of the enforcement of ethics and norms, this community service activity also aims to enhance community capacity through foreign language guiding training. This training is closely related to the implementation of ethics and norms, as tour guides play an essential role in conveying these values to visitors before the tour begins. The method employed is a school-based community field school, conducted through a series of socialization sessions, interactive discussions, and foreign language guiding training. The results indicate an improvement in the community’s understanding of the importance of preserving norms as part of sustainable tourism practices. The community not only succeeded in formulating village regulations but also began to apply the practice of conveying these rules to tourists during tours. This assistance has strengthened the community’s position as both the guardian of local wisdom and an active partner in guiding tourist behavior to align with local culture.